Development of a paediatric airway management checklist for the emergency department: a modified Delphi approach. Issue 4 (14th February 2023) - Miller, Kelsey A; Prieto, Monica M; Wing, Robyn; Goldman, Michael P; Polikoff, Lee A; Nishisaki, Akira; Nagler, Joshua
Abstract : Background: Airway management checklists have improved paediatric patient safety in some clinical settings, but consensus on the appropriate components to include on a checklist for paediatric tracheal intubation in the ED is lacking. Methods: A multidisciplinary panel of 14 experts in airway management within and outside of paediatric emergency medicine participated in a modified Delphi approach to develop consensus on the appropriate components for a paediatric airway management checklist for the ED. Panel members reviewed, modified and added to the components from the National Emergency Airway Registry for Children airway safety checklist for paediatric intensive care units using a 9-point appropriateness scale. Components with a median score of 7.0–9.0 and a 25th percentile score ≥7.0 achieved consensus for inclusion. A priori, the modified Delphi method was limited to a maximum of two rounds for consensus on essential components and one additional round for checklist creation. Results: All experts participated in both rounds. Consensus was achieved on 22 components. Twelve were original candidate items and 10 were newly suggested or modified items. Consensus components included the following categories: patient assessment and plan (5 items), patient preparation (5 items), pharmacy (2 items), equipment (7 items) and personnel (3 items). The components were formatted into a 17-item clinically usable checklist. Conclusions: Using the modified Delphi method, consensus was established among airway management experts around essential components for an airway management checklist intended for paediatric tracheal intubation in the ED.